Minat Beli Kopi Kenangan Dilihat Dari Citra Merek dan Kualitas Produk - Caelsiana Namba; Silva Nurramdany; Yolla Andriyani (Yayasan Literasi Sains Indonesia, 2022)
Increasing competition and the number of competitors requires business actors to pay attention to the needs and desires of consumers, and try to be able to fulfill these desires. Consumer behavior is an action taken by consumers in obtaining, using and determining products in making purchasing decisions (Tjiptono, 2009). Coffee is a type of global drink that is well-known in the world. Coffee is a very well-known plantation commodity throughout Indonesia, especially in Siak Regency. The culture of drinking coffee recently in Indonesia is on the rise. Currently, many coffee brands can be found on the market, such as: Janji Jiwa, Starbuck, Kulo, Jco Donut & Coffe, Kopi Kengan and many more. According to the Nielsen Company, Kopi Kenangan in 2019 is the brand with the number one top-of-mind awareness for the Milk Coffee category and the number two brand after the international coffee network for the general coffee category. Therefore the purpose of this study is to find out that the interest in buying coffee memories is seen from brand image and product quality. To find out this, a research was carried out using quantitative data which produced 117 respondents where the t test, f test, linear coefficient of determination test was carried out using the Spss 24 application. The results of this study can be concluded that the influence of the quality of memorable coffee products greatly influences purchase intention of consumers. consumers where the brand image of the memorable coffee product does not affect consumer buying interest due to the many brand images of coffee products in various places.